2007
DOI: 10.1158/0008-5472.can-07-2043
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of TMPRSS2 Gene Rearrangements in Multifocal Prostate Adenocarcinoma: Molecular Evidence for an Independent Group of Diseases

Abstract: Recurrent gene fusions between the androgen-regulated gene TMPRSS2 and the ETS family transcription factors ERG, ETV1, and ETV4 have been identified in the majority of prostate adenocarcinomas (PCA). PCA is often multifocal with histologic heterogeneity of different tumor foci. As TMPRSS2 is a common 5 ¶ partner of ETS gene fusions, we monitored TMPRSS2 rearrangement by fluorescence in situ hybridization (FISH) to study the origin and molecular basis of multifocal PCA heterogeneity. TMPRSS2 rearrangement was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
159
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(179 citation statements)
references
References 22 publications
(36 reference statements)
15
159
4
1
Order By: Relevance
“…As the incidence of ERG gene alterations have been linked to clinical stage and Gleason score, these differences may be explained, at least in part, by the distinct clinical compositions of the prostate tumor sets surveyed in each study, as suggested by Attard et al 8 Among our positive cases, deletion, rather than translocation, was found to be the main mechanism for TMPRSS2-ERG gene fusion in both transition zone prostate cancers (57%) and peripheral zone prostate cancers (58%), as previously reported in other studies. 2,24,25,33,40,41 We observed duplication of the rearranged sequence with deletion in one prostate cancer from the peripheral zone. Yoshimoto et al 3 observed duplication of TMPRSS2-ERG fusion in 6% of tumors and reported an association with worse prognosis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As the incidence of ERG gene alterations have been linked to clinical stage and Gleason score, these differences may be explained, at least in part, by the distinct clinical compositions of the prostate tumor sets surveyed in each study, as suggested by Attard et al 8 Among our positive cases, deletion, rather than translocation, was found to be the main mechanism for TMPRSS2-ERG gene fusion in both transition zone prostate cancers (57%) and peripheral zone prostate cancers (58%), as previously reported in other studies. 2,24,25,33,40,41 We observed duplication of the rearranged sequence with deletion in one prostate cancer from the peripheral zone. Yoshimoto et al 3 observed duplication of TMPRSS2-ERG fusion in 6% of tumors and reported an association with worse prognosis.…”
Section: Discussionmentioning
confidence: 77%
“…Tumors were considered spatially separate if they were Z3 mm from each others in any single section or Z4 mm from the closest cancer on the adjacent section above or below, as previously described. 25,26 For each cancer, Gleason score, tumor volume, extraprostatic extension, seminal vesicle involvement, surgical margin of resection status, and pathologic stage (pT) were separately recorded. Tumor volume at radical prostatectomy was calculated using the sum of the two largest tumor areas, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Similarly, the heterogenicity of TMPRSS2-ERG gene fusion in multifocal prostate cancer has also been investigated. 22,23 Nonetheless, further validation in large cohort studies is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…A final cohort of 142 cases was chosen based on availability of the appropriate paraffin blocks. Within each prostatectomy specimen, individual foci in specimens with multifocal prostate cancer were defined by the criteria of Mehra et al 54 Cancer foci that were separated by Z3 mm in a single section or separated by Z4 mm in adjacent blocks (above or below) were considered as separate foci. Each focus of prostate cancer was measured on the slides to obtain the largest dimension.…”
Section: Tma Constructionmentioning
confidence: 99%